2021
DOI: 10.1002/vms3.671
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the mutation rs8193069 in TLR4 to mastitis resistance and performance in Holstein cows in southern China

Abstract: Bovine mastitis has become increasingly important issues for farmers and consumers, leading to large economic losses in the dairy industry worldwide. Because treatment of mastitis is difficult and costly, improved mastitis resistance through selective breeding would be advantageous. The toll‐like receptor 4 (TLR4) is an important player in recognising pathogens and activating immune responses. However, its roles in mastitis occurrence and the underlying molecular mechanisms are unclear. In this study, a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…For instance, in most cases, different populations are characterized by high allele C frequency, which may be related to ongoing breeding work in the direction of increasing milk productivity parameters. The association of the C allele with the milk production traits of Holstein cows was confi rmed in a study by Chen et al (Chen H et al, 2021). At the same time, in the work of other authors, actually parity values of the C and T allele frequencies for this locus were revealed for Lithuanian Holstein cattle (Mišeikienė R et al, 2020).…”
Section: Discussionmentioning
confidence: 70%
“…For instance, in most cases, different populations are characterized by high allele C frequency, which may be related to ongoing breeding work in the direction of increasing milk productivity parameters. The association of the C allele with the milk production traits of Holstein cows was confi rmed in a study by Chen et al (Chen H et al, 2021). At the same time, in the work of other authors, actually parity values of the C and T allele frequencies for this locus were revealed for Lithuanian Holstein cattle (Mišeikienė R et al, 2020).…”
Section: Discussionmentioning
confidence: 70%
“…The time interval between vaccination and blood collection for each cow was of at least 30 days. Blood sample collection and hematology tests were performed as described previously [ 14 ]. To be more specific, blood samples from the cows were collected via coccygeal vein using a 10 mL disposable blood collection container for animals (SanMen MinSheng Medical Appliances Co., Ltd., Taizhou, China) connected to EDTA tubes (Wuhan Zhiyuan Medical Treatment Technology Co., Ltd., Wuhan, China).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Wang et al (143) reported that the LPS, which is considered an essential PAMPS, could be found in most gram-negative and some gram-positive bacteria that interact with TLR4 in mammary epithelial cells, which is why the higher expression of TLR4 has been noticed during mastitis in dairy cattle (143). A study reported that SNP-rs8193069 in the TLR4 gene was significantly associated with higher milk SCC (145,146). Similarly, another study found that the SNP-1,397-C-T at exon 3 of TLR4 correlated with milk SCS in Chinese Holstein, Sanhe cattle, and Chinese Simmental (145, 147).…”
Section: Toll-like Receptorsmentioning
confidence: 99%